(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2018)
Four Thousand Fish, curated by Kalari (South-West NSW) woman Emily McDaniel, is an exhibition that very precisely highlights the act of participation in sharing, shaping and taking responsibility in narratives. There are multiple overlapping aspects and commentaries that this exhibition touches upon; however, for the purposes of this review I am wanting to focus on how McDaniel goes about framing and shaping narrative, particularly with a narrative that has somewhat been hidden behind a colonial front, and highlight the importance of McDaniel’s telling of this story.